The role of regulation on bank competition and stability in ASEAN-5 countries / Abu Hanifa Md. Noman Alam - Abu Hanifa, Md. Noman Alam (2017)
Competition in banking industry has favourable outcomes in terms of efficiency, product diversification, financial innovation and financial inclusion. Whether competition is good or bad for bank stability is an issue of ongoing academic and policy debate, especially after the global financial crisis. Several studies have identified that regulatory oversight is one of the most important causes of the global financial crisis. However, to date, there has been no empirical evidence as to whether bank regulation shapes bank stability in competitive environment. The main objective of this study is to identify the moderating role bank regulation on the relationship between bank competition and bank stability in Association of Southeast Asian Nations (ASEAN) over the period of 1990- 2014. For the purpose of analysis, the main objective is divided into three parts. Firstly, examining the effect of bank competition on bank stability, secondly, identifying the moderating role of bank regulation on the relationship between bank competition and bank stability, and thirdly, analysing the influence of financial crisis on the moderating role of bank regulation on the relationship between bank competition and bank stability. The bank regulations considered in this study include capital regulation, activity restrictions, deposit insurance, and official supervision. Annual data on bank level variables, bank regulations and macroeconomic variables for five ASEAN countries – Indonesia, Malaysia, the Philippines, Singapore and Thailand – are compiled and analyzed. Two-step system Generalised Method of Moments (GMM) has been employed as estimation technique to bank level panel data. The results indicate that competition enhances bank stability by promoting solvency and capitalisation, and by reducing credit risk. Moreover, bank regulation moderates the relationship between bank competition and bank stability. Among bank regulations, this thesis found that activity restrictions are most effective bank regulation in promoting bank stability in competitive environment, while deposit insurance found most effective bank regulation in promoting bank stability in less competitive environment. Furthermore, the moderating roles of bank regulation on the relationship between bank competition and bank stability are found remained unchanged during the financial crisis except deposit insurance. The results have several policy implications for policy makers and regulators. Firstly, the policy makers should avoid anticompetitive policies as competition promotes bank stability. Secondly, activity restrictions work well only in the competitive market, while deposit insurance enhances bank stability only in less competitive markets. Thirdly, deposit insurance found effective to keep banks stable in competitive market during crisis period.